PENINGKATAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) MELALUI EDUKASI INTERAKTIF DAN DEMONSTRASI CTPS PADA SISWA SDN 05 SURAU GADANG KOTA PADANG - Uthia, Rahimatul (PITIMAS: Journal of Community Engagement in Health, 2025)
Clean and Healthy Living Behavior (PHBS) is a fundamental strategy in preventing environment-based diseases. School-aged children represent an effective target group for health promotion interventions. This program aimed to improve students’ knowledge and skills regarding PHBS, especially handwashing with soap following the WHO's six-step technique. Conducted in October 2024 at SD 05 Surau Gadang, Padang, the activity involved interactive education, demonstration, hands-on practice, and educational games. Eightyfive students participated. Evaluation using pre–post tests and observational checklistsshowed an increase in knowledge (from 54.3 to 87.6) and correct handwashing performance (92%).These findings align with prior studies demonstrating the effectiveness of interactive health promotionon student hygiene behavior (Freeman et al., 2014; Rabie & Curtis, 2006). This program is recommendedfor continuous implementation to strengthen school health promotion.